Inositol hexakisphosphate kinases differentially regulate trafficking of vesicular glutamate transporters 1 and 2 - Li, Haiyan; Datunashvili, Maia; Reyes, Reno C.; Voglmaier, Susan M. (Frontiers in Cellular Neuroscience, 2022)
Inositol pyrophosphates have been implicated in cellular signaling and membrane trafficking, including synaptic vesicle (SV) recycling. Inositol hexakisphosphate kinases (IP6Ks) and their product, diphosphoinositol pentakisphosphate (PP-IP5 or IP7), directly and indirectly regulate proteins important in vesicle recycling by the activity-dependent bulk endocytosis pathway (ADBE). In the present study, we show that two isoforms, IP6K1 and IP6K3, are expressed in axons. The role of the kinases in SV recycling are investigated using pharmacologic inhibition, shRNA knockdown, and IP6K1 and IP6K3 knockout mice. Live-cell imaging experiments use optical reporters of SV recycling based on vesicular glutamate transporter isoforms, VGLUT1- and VGLUT2-pHluorins (pH), which recycle differently. VGLUT1-pH recycles by classical AP-2 dependent endocytosis under moderate stimulation conditions, while VGLUT2-pH recycles using AP-1 and -3 adaptor proteins as well. In electrophysiological experiments we measure glutamate signaling with short stimuli and under the intense stimulation conditions that trigger bulk endocytosis. Using a short stimulus to release the readily releasable pool (RRP), we show that IP6K1 KO increases exocytosis of both VGLUT1- and VGLUT2-pH, while IP6K3 KO decreases the amount of both transporters in the RRP. IP6K1 KO increases synaptic facilitation and IP6K3 KO decreases facilitation compared to wild type in CA1 hippocampal Schaffer collateral synapses. After intense stimulation, the rate of endocytosis of VGLUT2-pH, but not VGLUT1-pH, is increased by knockout, knockdown, and pharmacologic inhibition of IP6Ks. Thus IP6Ks differentially affect the endocytosis of two SV protein cargos that use different endocytic pathways. However, while IP6K1 KO and IP6K3 KO exert similar effects on endocytosis after stimulation, the isoforms exert different effects on exocytosis earlier in the stimulus and on the early phase of glutamate release. Taken together, the data indicate a role for IP6Ks both in exocytosis early in the stimulation period and in endocytosis, particularly under conditions that may utilize AP1/3 adaptors.